Non-genetic factors affecting growth of Ethiopian Boran cattle - Kassa-Mersha, H.; Arnason, T. (1986)
It is well accepted that the growth rate of beef animals affects the economic returns of commercial ranchers. The aim of this study was therefore to investigate the effects of certain environmental factors on the birth weight and growth in a herd of Boran cattle bred at the Adamitulu cattle Improvement Ranch in Ethiopia. The data consisted of weight records on 4,021 (2037 male and 1984 female) animals during the years 1961 – 1984. Observations on both the birth weight and the weaning weight of 3959 calves of the known percentage were used for statistical analysis. The uncorrected average birth weight and weaning weight of 4021 individual calves was found to be 23.5 kg and 170.2 kg respectively. The average daily gain from birth to weaning was 563 grams/day. The birth weight of the Boran cattle under present study is significantly affected by the systematic environmental factors sex and birth year. The preweaning growth is significantly affected by the following non-genetic factors: sex, birth year, season, parity and age of meaning. The post weaning growth is clearly affected by sex, birth year and season. Therefore, when estimating genetic parameters and breeding values of growth traits adjustment should be made for these non-genetic factors. Gestation length, age at first calving and calving interval was calculated as 280.14±4.99, 1247±213 and 448.4±112.6 days respectively with average 76.1% calving rate. Average calf mortality rate of 3.78%, 1.44% and 1.49% were found for age periods of 0-8 months, 8-12 months and 12-18 months, respectively.